Building characteristics and energy use of energy-efficient renovated offices - Minyoung Kwon (A+BE: Architecture and the Built Environment)
Chapter 2 presented the physical and psychological satisfaction parameters for user-focused evaluation. In most renovation projects, the façade is a major consideration next to the HVAC system to optimise the performance of the building. Many studies reveal that façade renovation has a large impact on the energy efficiency. The aim of this chapter is to identify the characteristics of renovated offices, such as façade types, HVAC system, and sun shading, and compare the energy performance based on user typologies in renovated and non-renovated office buildings.